(untitled) (Albayan Scientific Journal, 2023)
This study is intended to shed light on one of the dry valleys in the suburbs of Tobruk. To that end, it studies and analyze its hydrological potential in the light of climatic data, as an attempt to exploit the water surplus of the basin in the developing such potential agriculturally and pastorally. In this regard, the study has examined the hydrological characteristics of the basin with the area of 3.61 km²,Based on the climatic data of Tobruk Station during the period 1984-2017, it has become obvious that the prevailing climate was almost dry, and the rainfall rate was 176.3 mm / year, Mathematical coefficients have been employed to calculate the water surplus that reached 67 mm Distributed between surface running water, natural recharge of groundwater, evaporation – potential transpiration reached the annual total of 297.6 mm. And the water budget of the basin that covers an aggregate area of 636443 m3 / year, at the end, the study has come up with these findings. First, the water surplus formed the rate of 5.97% only, whereas, The leakage during the time of deceleration, and steady leakage, was 0.03%, Second, The bulk of rainwater is lost by evaporation, which reaches the rate of 94%. Third, the amount of runoff in the basin after the fall of winter rain was 37993 m3.